Pengaruh Metode Latihan Drill Terhadap Keterampilan Dasar Chest Pass Bola Basket Siswa Ekstrakurikuler di SMA Negeri 1 Sukatani - Soederajat Soederajat; Dhika Bayu Mahardhika; Rizky Aminudin (Universitas Singaperbangsa Karawang, 2022)
The purpose of this study was conducted to determine whether there is an influence of drill training methods on basic chest pass skills in basketball games. To answer the formulation of this study, researchers use a quantitative approach with experimental methods. The study was conducted at SMA Negeri 1 Sukatani with the type of purposive sampling of the population taken was students who participated in basketball extracurricular activities with a total of 1,144 students and a sample of 38 male and female students. The research design that the author used was a one group pretest – posttest model. The results of the study were obtained using a normality test with the results obtained in the pretest of 0.024 > 0.05 and a posttest of 0.033 > 0.5 from the results of the study showing normally distributed data and through homogeneity test calculations which showed a sig sig value of 0.055 > of 0.05 that the data from the pretest-posttest results stated that the data were homogeneous distributed and t-test calculations obtained sig values. (two-tilled) 0.000 < 0.05 indicates a significant difference between the results before and after treatment. The conclusion from the results of the research conducted can be stated that there is an influence of the drill training method on the basic skills of chest pass in basketball extracurricular activities at SMA Negeri 1 Sukatani.